Architectural Restoration of the Tegalsari Grand Mosque, Jetis, Ponorogo, East Java (1994–1997 CE) - Adhelia Shelyn Levinanda; Himayatul Ittihadiyah (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
The Tegalsari Grand Mosque is a cultural heritage structure protected under Indonesian Law No. 11 of 2010; however, it has not yet been formally designated by the Government of Ponorogo Regency. A major renovation undertaken by the local government in 1978 substantially altered the mosque’s original form, resulting in the erosion of its distinctive Old Javanese architectural identity. This study investigates the historical background of the restoration of the Tegalsari Grand Mosque, the factors that motivated the restoration, and the outcomes achieved through this process. Specifically, the research addresses how and why restoration efforts were carried out to recover the mosque’s original architectural character. Employing a historical research method, the study follows the stages of heuristics, source verification, interpretation, and historiography, drawing upon both primary and secondary sources. The concept of architectural restoration serves as the principal analytical framework. The findings demonstrate that the mosque was founded in 1742 CE by Kiai Ageng Muhammad Besari in Gendol Hamlet, Tegalsari Village, Jetis District, Ponorogo Regency, and originally embodied the characteristics of Old Javanese Mosque architecture. Restoration was initiated by the Cultural Heritage Preservation Agency between 1994 and 1997, following the gradual decline of the mosque’s identity as an ancient Javanese mosque. The restoration was implemented in three phases, encompassing the main prayer hall, the veranda and pavilion, and the courtyard along with its supporting structures, ultimately reaffirming the mosque’s historical and architectural significance.